NILAI-NILAI PENDIDIKAN DALAM FAWATIH AL-SUWAR - Yunus, Ahmad (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
Fawatih al-suwar is the preamble or beginning of the surahs in the Qur'an because of its position that initiates the passage of texts in a Letter of the Qur'an. Of the 114 letters in the Qur'an, there are 29 letters beginning with al-ahruf al-muqaththa'ah. Al-ahruf al-muqaththa'ah consists of a portion of the Hijaiyah letters. As is known the letters, the Hijaiyah letters in arabic consist of 28 letters, or in other opinions 29 letters if the letters ال are part of the letters. Of the 28 letters, 14 of them are part of al-ahruf al-muqaththa'ah.  Namely: ق، ط، س، ر، ح، ا، ي ل، ن، م، ل، ع، ه، ك،.  Al-ahruf al-muqaththa'ah is a separoh of the Hijaiyah letter, a part of the letter hams is al-ahruf al- muqaththa'ah.  In Fawatih al-suwar, it is depicted that the technique of opening up good lessons, so as to arouse the interest and motivation of students in learning. In addition to the technique of opening lessons, the educational value contained in fawatih al-suwar is the giving of praise/reward and punishment/punishment.  This can be seen in the opening of the Qur'an letter using praise and verdict. Another educational value contained in fawatih al-suwar is the method of giving questions.